Subdural tuberculous abscess of the lumbar spine in a patient with chronic low back pain - Mikić Dragan; Roganović Zoran; Ćulafić Slobodan; Rajić-Dimitrijević Radmila; Begović Vesna; Milanović Milomir (Vojnosanitetski Pregled)
Introduction. Despite modern imaging methods, tuberculous abscess in the subdural space of the spine can lead to misdiagnosis and to neurogical complications development, even more up to paraplegia. We presented an extremely rare case of subdural tuberculous abscess of the lumbar (L) spine and paraparesis in imunocompetent a 49-year-old patient. Case report. A patient with chronic L syndrome and a history of intervertebral (IV) disc L3 and L5 operations got severe back pain late in July 2007. At the same time the patient had a purulent collection in the left knee, and was treated with high doses of corticosteroids and antibiotics. Then, the patient got a high fever, the amplification of pain in the L spine and the development of paraparesis. Erythrocyte sedimentation rate was 108 mm/1 h, Creactive protein 106.0 mg/L, white blood cell (WBC) 38.4 x 09/L with a left turn. Magnetic resonance imaging (MRI) of the spine was registered expansive formation in the spinal canal, from the level of the IV disc L2 to the mid-L4 vertebral body. This finding is a “spoke” in favor of the extrusion and sequestration of IV disc L3 with the cranial and caudal migration. The patient underwent an emergency neurosurgical operation. The diagnosis of subdural staphylococcal abscess of L spine was made. According to the antibiogram antibiotic therapy was applied but without effect on the course of the disease. Control MRI of the L spine showed spondylodiscitis L3/L4, abscess collection in the spinal canal and paravertebral muscle abscess. Late in September 2007 the patient underwent needle biopsy of the L3 vertebral body guided by computed tomography and the acid-fast bacilli (AFB) were found. Tuberculostatics were introduced in the therapy. Two years later the patient was without significant personal difficulties, and with normal clinical, laboratory and morphological findings. Conclusion. Subdural tuberculous abscess of the spine is extremely rare manifestation of spine tuberculosis. The exact and early diagnosis and adequate treatment of atypical form of spine tuberculosis are key factors of good prognosis.